Incidente de desconsideração da personalidade jurídica - Souza, Bruna Casemiro (2018)
The present work deals with due process to the Disregard of the Legal Personality, whose scope is to demonstrate a panorama of the contours of material law of the theory and analysis of its effectiveness within the jurisdictional process, presenting the normatization inaugurated by the New Code of Civil Procedure. The issue in question is of the utmost importance, given that the disregard of the legal entity aims to protect third parties from the illicit use of the principle of autonomy of assets between the spheres of the legal entity and its partners. That is to say, the company's equity obligations can be realized through the acquisition of shareholders 'or managers' equity, when this is shown to be a misuse of purpose or an asset mismatch. Disregard is also possible in the reverse mode, this occurs when pursuing the equity of the company to meet the obligation of one of its partners, evidently when it is found that the legal entity was used as a shield of legitimate claims of third parties in the face of one or more of its members. In addition, art. 50 of the Civil Code houses what the doctrine named a major or subjective theory of disregard, requiring for the removal of legal personality two requirements: abuse of personality and injury to third. Already the art. 4 of Law 9.605/98 and art. 28, §5, of the CDC, establish the so-called minor or objective theory, where for the realization of the disregard of the legal entity would be enough the occurrence of the loss to the creditor. Finally, based on the fact that nothing destroys a legal entity more than the damage that can be caused by its own members, the applicability of this theory would function as a way to strengthen the values pertaining to dignity and respect to the human being